Fungsi dan Kedudukan Bahasa Mandarin di Indonesia - Sutami, Hermina (UI Scholars Hub, 2023)
Since Political Reformed in 1998, teaching of Mandarin language burst out everywhere. Many schools— from primary until senior high school, even kindergarten—teach Mandarin. Having skill in Mandarin has become one prerequisite for new employees recruitment. In order to anticipate this situation, many schoolmasters without having understanding about our National Language Political Policy thought that Mandarin should be taught. They do not know that after nearly 30 years Mandarin was prohibited, the teaching Mandarin planning is really hard to be realised. There is no Mandarin language teacher, text book for Indonesian students, curriculum and syllabus, etc. In fact, many schools try to find old people who were educated in Chinese Schools before the era of late President Suharto to teach Mandarin. The result is far from what they expect. The Department of Education and Culture tried to overcome these problems, but there are still many problems facing us. This paper tried to show the problems, and gave suggesstion to overcome.